ANALISIS KETERAMPILAN BERBICARA PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA KELAS III UPTD SD NEGERI AFALSIA - Yulia Anika Jemau; Antonius A. Saetban; Jon A. Lalang Yame (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to analyze the speaking skills of third-grade students at the Afalsia State Elementary School (UPTD SD Negeri Afalsia) in the Indonesian Language subject. The study employed a qualitative descriptive approach with 15 third-grade students as participants. Data were collected through participatory observation, interviews, and documentation. The indicators analyzed included vowels and consonants, intonation, accuracy of pronunciation, word sequencing, and fluency. The results showed that the students’ speaking skills were in the “good” category, with an average percentage of 85%. The vowel aspect scored 88%, intonation 82%, accuracy 78%, word order 86%, and fluency 91%. Factors influencing speaking skills include self-confidence, practice opportunities, family environment, and teacher learning strategies. These findings indicate the need for continuous speaking practice to optimize the communication skills of elementary school students.